Patrocinio de marcas y los Derechos de Imagen: qué está cambiando en el deporte universitario de Estados Unidos y el caso de Messi - Antequera, Ricardo E. (2025)
This study delves into how brand sponsorship and image rights are reshaping the sports industry, with a particular focus on Lionel Messi’s role in Inter Miami of the MLS. It examines the growing economic importance of image rights and the influence of legislative measures such as the Pelé Law and the NCAA v. Alston case on athletes’ image rights. Furthermore, it highlights the impact of NIL laws in U.S. college sports and the role of social media in athletes’ image monetization.